Penerapan Metode Hypnoteaching dalam Pembelajaran Tematik Kurikulum 2013 untuk SD/MI Sederajat - Inchinia Rowin (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2015)
Facing such a competitive era in the coming years, make Indonesian government launched a new curriculum that is Curriculum 2013. It brings a concept that students are required to be more independent and explore themselves in more detail material. It is the development of the basic concept of Thematic learning which is an integrated learning that uses themes to link some subjects so as to provide meaningful experiences to the students. It is also a necessary for an application of integrated methods that can support thematic learning, to be able to give success to the students, one of them is Hypnoteaching method. It is a method using a combination of teaching involves the conscious and subconscious mind by way of giving learners a suggest. Teachers use a persuasive and easily understood language as a communication tool in accordance with the expectations of learners. One of the main benefits is the learning process will more fun so that the ability of children to capture the materials will be easier and lighter and do not feel in pressure.